Living birth following preimplantation genetic testing for monogenic disorders to prevent low-level germline mosaicism related Nicolaides–Baraitser syndrome - Pan, Jiexue; Li, Jie; Chen, Songchang; Xu, Chenming; Huang, Hefeng; Jin, Li (Frontiers in Genetics, 2022)
Objective: Paternal sperm mosaicism has few consequences to fathers for mutations being restricted to sperm. However, it could potentially underlie severe sporadic disease in their offspring. Here, we present a live birth of female infant from a father with low-level sperm DNA mosaicism achieved by prenatal genetic testing for monogenic disorders (PGT-M). Methods: The couple with father carrying sperm DNA mosaicism received standard in vitro fertilization treatment, with intracytoplasmic sperm injection, embryo biopsy, polymerase chain reaction and DNA analysis. Only 1 unaffected embryo was transferred to the uterine cavity. Amniocentesis was performed at the 16th week of gestation by copy number variation-seq, karyotyping and Sanger sequencing. Results: Eight surviving embryos were biopsied on the blastocyst stage. Karyomapping and Sanger sequencing were applied to detect the euploidy and paternal mutation. After performing PGT-M followed by successful pregnancy, the prenatal genetic diagnoses revealed that fetus was unaffected, and one healthy girl was born. Conclusion: This is the first reported live birth with unaffected children achieved by PGT for a germline mosaicism father. It not only opens the possibility on preventing the recurrent monogenic disease of children among gonadal mosaicism families, but also alerts clinicians to consider the gonadal mosaicism as the source of DMNs.